2016
DOI: 10.1111/njb.01133
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic notes on Tragopogon, and two newly described taxa from Anatolia

Abstract: Tragopogon L. (Asteraceae) includes several cryptic species that are geographically widespread and morphologically similar. Here, we describe two new native species from eastern Anatolia. Through both morphological and molecular data, we present diagnostic characteristics, descriptions, pollen grains and micro‐ and macro‐morphological properties of achenes, as well as the conservation status of the newly described species. Current morphological and molecular results support treating T. reticulatus Boiss. & Hue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…longirostris from T. porrifolius as previously suggested by Greuter (2003). Gültepe et al (2016) also made similar taxonomical comment about T. longirostris var. longirostris.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…longirostris from T. porrifolius as previously suggested by Greuter (2003). Gültepe et al (2016) also made similar taxonomical comment about T. longirostris var. longirostris.…”
Section: Discussionsupporting
confidence: 83%
“…Coşkunç and M.Gultepe) contrary to Greuter (2003). Besides Gültepe et al (2016) reported, contrary to Greuter (2003), that T. porrifolius and T. longirostris should be treated as separate species based on molecular data. Correspondingly, the aim of the present study is to identify the authentic material of the name T. longirostris var.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Meanwhile the related literature (Behçet, 2001;Doğan and Akaydın, 2004;Özgökçe et al, 2005;Sutorý, 2005;Akan et al, 2008;Karabacak and Behçet, 2009;Dirmenci et al, 2010;Eker and Babaç, 2010;Yıldırım et al, 2011;Yıldız et al, 2011;İlçim et al, 2013;Vitek et al, 2014;Yıldırırm, 2014;Doğan et. al., 2015;Tekşen and Karaman, 2015;Fırat and Yıldız, 2016;Gültepe et al, 2016;Fırat, 2017a,b;Pınar, 2017) concerning the endemic plant taxa of Van Lake basin were also traced, and an endemic plant list with 259 taxa was created. Collection localities are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…1977), a sectional classification was not proposed in the Turkish Tragopogon account by Matthews (1975). However, Gültepe et al (2016) suggested that Turkish Tragopogon species should be treated under eight sections according to Borisova's (1964) system. Following Borisova (1964), T. olympicus should be treated under Tragopogon sect.…”
Section: Author Contributionsmentioning
confidence: 99%